Provisions for liabilities versus the financial security of dairy cooperatives - Ganc, Marzena (Rezerwy na zobowiązania a bezpieczeństwo finansowe spółdzielni mleczarskich, 2020)
The main objective of the study is to determine the financial security of dairy cooperatives depending on the level of provisions for liabilities created, i.e. to answer the research question: does the level of provisions determine the financial security of dairy cooperatives? Dairy cooperatives in Poland, in which provisions for liabilities were created, were chosen in a targeted manner. The breakdown into groups was carried out using the quartiles method (assuming the level of provisions for liabilities as a criterion), and then the test for the significance of the Kruskall-Wallis differences was applied due to the greater than two groups isolated for analysis. The research hypothesis is as follows: the value of provisions for liabilities determines the level of financial security of dairy cooperatives. The research period covered 2012-2016. Financial liquidity, management efficiency and overall debt ratios were calculated. A relationship was found between the value of provisions for future liabilities and the level of liquidity ratios assessed. The larger the cooperative in terms of the isolated criterion, the higher the current, quick and immediate liquidity
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 2, s. 45-55
Keywords: dairy cooperatives; liquidity; provisions for liabilities; spółdzielnie mleczarskie; płynność finansowa; bezpieczeństwo finansowe; rezerwy na zobowiązania